Quality Control in Coconut Sorting Process using Statistical Process Control (SPC) and Root Cause Analysis (RCA) (Case Research: UMKM Wika Kelapa) - Ramdan Nugraha; Yani Iriani (Journal Research of Social Science, Economics, and Management, 2025)
UMKM Wika Kelapa is a coconut shell (endocarp) supplier business in Pangandaran. The main problem faced is the high level of coconut defects, including broken coconuts, rotten coconuts, and sprouted coconuts, with an average percentage of 4.65%, exceeding the 3% tolerance limit that has been set. The high level of defects impacts business losses because defective coconuts are sold at lower prices. This research aims to determine whether quality control in the coconut sorting process is in control, identify factors causing defects, and provide suggestions for improvement to minimize coconut defects using Statistical Process Control (SPC) and Root Cause Analysis (RCA) methods. The sorting process is illustrated using the SIPOC (Supplier, Input, Process, Output, and Customer) approach. The results of SPC analysis using check sheets, histograms, Pareto diagrams, and P-Charts show that the coconut sorting process is not yet statistically controlled, with seven points outside the control limits, namely January (0.050), March (0.051), April (0.052), June (0.056), August (0.035), September (0.042), and November (0.040) during 2024. The RCA analysis using fishbone diagrams and five-whys revealed that broken coconut defects are dominantly caused by human factors, including lack of accuracy, unskilledness, and worker fatigue. Rotten coconut defects are dominantly caused by method factors, namely the absence of SOPs, resulting in prolonged storage in humid and unhygienic conditions. Sprouted coconut defects are primarily caused by method factors due to lack of SOPs or training on storage and absence of inspection protocols.